THE GREEN SYNTHESIS, CHARACTERIZATION AND EVALUATION OF ANTIOXIDANT AND ANTIMICROBIAL EFFICACY OF SILVER&GOLD NANOSPHERES SYNTHESIZED FROM WHEAT BRAN - Gupta, Sonika (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Abstract In the present scenario, biogenic production of gold and silver nanoparticles has evoked considerable interest in terms of their diverse biomedi0058cal applications because of their extremely small size and large surface to volume ratio. Hence, the aims of the current study were to use plant extract for the biosynthesis of silver and gold nanoparticles and to evaluate their antibacterial and antioxidant activity in vitro. First, aqueous silver nitrate and chloroauric acid solutions have been treated with Wheat bran extract;reduction of the silver and chloroaurate ions is witnessed resulting in the formation of highly stable silver and gold nanoparticles in solution. Characterization of synthesized silver and gold nanospheres is made using UV-visible,SEMandTEManalysis, indicated that they ranged from 30 to 55 nm and 45 to 70 nm in size respectively.Â The free radical scavenging potential has been investigated using DPPH assay, examined by a UV-visible spectrophotometer and found that AgNPs AuNPs exhibited exceptional potential- compared to wheat bran extract alone. Antimicrobial efficacy against dental disease causing pathogens - Staphylococcus aureus (MTCC 7443) and Streptococcus mutans (MTCC 497) was tested using agar diffusion method. The synthesized AgNPs and AuNPs efficiently inhibited the growth of respective pathogens. It could be concluded that these nanospheres can be act as potent antioxidant and antimicrobial agents for commercial application. Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords: AgNPS, AuNPS, Wheat Bran, DPPH Scavenging Assay, Antioxidant Activity, Antimicrobial Activity, SEM, TEM Â Â Â Â Â